Method for preparing super-hydrophobic composite film layer on surface of aluminum alloy

By using microarc oxidation method to form a porous oxide film on the surface of the aluminum alloy, and depositing a cerium octadecanate coating with electrochemical deposition method, the wear and corrosion problems of aluminum alloy in complex working conditions are solved, and a high-performance superhydrophobic composite film layer is achieved.

CN119663398APending Publication Date: 2025-03-21CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411878314.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Aluminum alloys are prone to wear failure or corrosion damage in complex working conditions, and the weather resistance and bonding performance of the existing superhydrophobic film layers are poor.

Method used

A porous oxide film was formed on the surface of the aluminum alloy by microarc oxidation, and a cerium octadecanoate coating was deposited on its surface by electrochemical deposition to form a MAO/ED superhydrophobic composite film layer.

Benefits of technology

It improves the wear resistance, corrosion and superhydrophobic properties of aluminum alloys, enhances the durability and bonding properties of the film, and is suitable for complex working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663398A_ABST
    Figure CN119663398A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a super-hydrophobic composite film layer on the surface of an aluminum alloy micro-arc oxidation film, and belongs to the field of metal material surface modification. Firstly, the aluminum alloy surface is pretreated and cleaned; then preparing electrolyte, taking an aluminum alloy sample as an anode, taking a stainless steel barrel as a cathode, and firstly preparing a porous oxidation film layer on the surface of the aluminum alloy by adopting a micro-arc oxidation process; and then a super-hydrophobic film layer (micro-arc oxidation ceramic film / cerium octadecanoate composite film layer) with a micro-nano coarse structure is obtained on the aluminum alloy micro-arc oxidation film layer through an electrochemical deposition method. Compared with a traditional method for preparing the super-hydrophobic film layer, the method has the advantages that the super-hydrophobic film layer with the water contact angle exceeding 150 degrees can be obtained without low-energy modification, and in addition, the surface of the micro-arc oxidation film layer can be effectively sealed. The method has the advantages of simple process operation, high treatment efficiency, controllable coating thickness and the like, and is easy to popularize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of surface modification of metal materials, and in particular to a method for preparing a super-hydrophobic composite film layer on the surface of an aluminum alloy. Background Art

[0002] With the continuous development of the economy and society, people's living standards are gradually improving. However, while human society has achieved great economic prosperity, environmental pollution has become a problem that needs to be solved urgently. Lightweight design and technology is one of the main technical solutions to solve the above problems, and has become a strategic goal in fields such as engineering design and materials engineering. At the same time, lightweight materials are widely used in various fields such as aerospace, rail transportation, automobiles, and shipbuilding.

[0003] In addition to the general properties of aluminum, aluminum alloys also have some specific properties of alloys due to the different types and quantities of alloying elements added. The density of aluminum alloys is 2.63~2.85g / cm 3 , has higher strength (tensile strength σ b 110~650MPa), is one of the most representative lightweight materials. At the same time, aluminum alloy has good electrical and thermal conductivity, good corrosion resistance and weldability, can be used as structural materials, and has a wide range of applications in aerospace, aviation, transportation, construction, electromechanical, light chemical and daily necessities. However, when used as a structural material, the oxide film naturally formed by aluminum alloy is prone to wear failure or corrosion damage under complex working conditions (such as severe wear, strong corrosion and other conditions) due to its limited density and thickness, resulting in the phenomenon of oxide film shedding, which seriously affects the service performance and safety performance of aluminum alloy structural parts. Therefore, it is necessary to perform surface protection treatment on aluminum alloy to improve the wear resistance and corrosion resistance of aluminum alloy structural parts. In addition, for aluminum alloy structural parts for aviation, if they have surface hydrophobic and super hydrophobic properties, they can effectively improve their service performance such as corrosion resistance, self-cleaning and anti-icing, which will greatly improve the reliability and flight safety of aircraft.

[0004] The main surface treatment methods for aluminum alloys include chemical oxidation, anodizing and micro-arc oxidation. As a new type of environmentally friendly surface treatment technology, micro-arc oxidation relies on the instantaneous high temperature and high pressure generated by arc discharge on the surface of valve metals such as aluminum, magnesium, titanium and their alloys to grow a ceramic film layer mainly composed of matrix metal oxide. However, during the micro-arc oxidation process, micro-arc discharge and a large number of bubbles emerge on the surface of the sample, which makes it easy to form defects such as micropores and microcracks in the produced film layer, resulting in low density of the micro-arc oxidation film layer, which limits its further improvement in performance. In order to solve this problem, the porous micro-arc oxidation film layer can be sealed through subsequent treatment processes to improve its density. These processes include boiling water and steam sealing method, hydrolyzed salt sealing method, dichromate sealing method, filling sealing method and other methods.

[0005] For the preparation of super-hydrophobic film layers, etching, anodization, hydrothermal reaction, electrodeposition and other methods can be used to prepare micro-nano rough structures on the surface of the material, and then modified with low-energy substances. However, the super-hydrophobic film layers prepared by this preparation method often have poor weather resistance, and the binding performance of low-energy substances and rough surfaces is also poor. The film layer modified with low energy is easy to lose super-hydrophobic properties during service (such as scratching, wear, high temperature, corrosion and other environments).

[0006] The present invention combines micro-arc oxidation with electrodeposition technology, and adopts a composite method to prepare a new type of wear-resistant, corrosion-resistant and super-hydrophobic composite film layer, which not only retains the excellent properties of the micro-arc oxidation film layer such as high wear resistance and corrosion resistance, but also obtains super-hydrophobic properties. At the same time, the composite super-hydrophobic film layer has better weather resistance and bonding performance than the traditional low-energy modified surface film layer. In addition, the composite method can also achieve the sealing treatment of the micro-arc oxidation film layer.

[0007] At present, there are few reports on the research of combining micro-arc oxidation and electrochemical deposition on the surface of aluminum alloy to prepare super-hydrophobic composite film. The present invention performs micro-arc oxidation on aluminum alloy and then performs electrochemical deposition to prepare a new type of wear-resistant, corrosion-resistant and super-hydrophobic composite film, which improves the self-cleaning, anti-icing and corrosion resistance of aluminum alloy and has certain innovation. Summary of the invention

[0008] The present invention aims to develop a method for preparing a super-hydrophobic composite film layer on the surface of an aluminum alloy, so that the surface of the aluminum alloy micro-arc oxidation film layer has super-hydrophobicity, thereby improving the self-cleaning, anti-icing, and corrosion resistance properties of the aluminum alloy.

[0009] To achieve the above purpose, the specific process of the present invention is as follows:

[0010] (1) Surface pretreatment of aluminum alloy: The aluminum alloy substrate was cut into appropriate size, and then its surface was mechanically polished with sandpaper. The sample was cleaned and dried with cold air.

[0011] (2) Micro-arc oxidation treatment: Prepare a silicate solution containing a certain concentration, stir it thoroughly to make it evenly mixed, use the aluminum alloy sample pretreated in step (1) as the anode, and use but not limited to stainless steel as the cathode. The micro-arc oxidation process uses but is not limited to a constant voltage mode, sets the voltage to 200-500V, and the time to 5-30min, and performs micro-arc oxidation treatment on the sample to obtain a porous micro-arc oxidation film layer with a thickness of not less than 6μm on the surface of the aluminum alloy.

[0012] (3) Electrodeposition treatment: 0.075 mol / L cerium nitrate hexahydrate (CeN3O9·6H2O), 0.3 mol / L octadecanoic acid (C 18 H32 O2), a mixed solution of anhydrous ethanol and deionized water, the aluminum alloy with a micro-arc oxidation film layer on the surface obtained in step (2) is used as a cathode, and a graphite sheet is used as an anode but is not limited to it. The solution temperature is 20-80°C, and electrochemical deposition is performed at a voltage of 30-60V for 0.1-0.5h to obtain a MAO (micro-arc oxidation) / ED (electrodeposition) super-hydrophobic composite film layer.

[0013] The aluminum alloy surface micro-arc oxidation / electrodeposition super-hydrophobic composite film layer (micro-arc oxidation ceramic film / cerium octadecanoate) prepared by the method of the present invention has a micro-nanoscale rough structure on the surface, and the contact angle of deionized water on the surface of the super-hydrophobic composite film layer is 152.2°~155.6°, and the rolling angle is 4~7°.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] (1) The micro-arc oxidation method and electrochemical deposition method adopted in the present invention have short reaction time, high efficiency and are easy to promote and apply.

[0016] (2) The super-hydrophobic film layer obtained by the present invention does not require low-energy modification, the film layer has better durability, and plays a role in sealing the micro-arc oxidation film layer.

[0017] (3) The present invention prepares a super-hydrophobic coating on the surface of the aluminum alloy micro-arc oxidation film layer, has no special requirements on the shape and size of the sample, and has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the SEM image of the surface of the micro-arc oxidation film on aluminum alloy;

[0019] Figure 2 This is a 200x SEM image of the aluminum alloy micro-arc oxidation ceramic film / cerium octadecanoate super-hydrophobic composite film surface;

[0020] Figure 3 This is a 2000x SEM image of the aluminum alloy micro-arc oxidation ceramic film / cerium octadecanoate super-hydrophobic composite film surface;

[0021] Figure 4 is the static contact angle of deionized water on the surface of aluminum alloy micro-arc oxidation film;

[0022] Figure 5 It is the static contact angle of deionized water on the surface of aluminum alloy micro-arc oxidation ceramic film / cerium octadecanoate superhydrophobic composite film. Specific embodiments

[0023] The present invention will be further described below in conjunction with the accompanying drawings.

[0024] The purpose of the present invention is to develop a method for preparing a composite film layer with super-hydrophobic functional properties on a micro-arc oxidation film layer on an aluminum alloy surface. To achieve the above purpose, the present invention uses 7075 aluminum alloy as a substrate and forms a porous oxide film on the aluminum alloy surface by a micro-arc oxidation method; then a certain concentration of cerium nitrate hexahydrate and octadecanoic acid solution are prepared, and an octadecanoic acid cerium coating with super-hydrophobic functional properties is obtained on the aluminum alloy micro-arc oxidation film layer by an electrochemical deposition method at different voltages and times.

[0025] Embodiment 1

[0026] (1) Surface pretreatment of aluminum alloy: The aluminum alloy substrate was cut into samples of 25 mm × 25 mm × 1 mm, and then the surface was mechanically polished using 240#, 600#, 1000#, 1500#, and 2000# SiC sandpaper in sequence. The samples were then ultrasonically cleaned in deionized water and anhydrous ethanol for 10 min in sequence to remove surface debris and oil stains. The samples were then taken out and dried with cold air.

[0027] (2) Micro-arc oxidation treatment: 2L Na2SiO 3、 The aqueous solution of NaOH and NaF was stirred thoroughly to make it uniformly mixed. The aluminum alloy sample pretreated in step (1) was used as the anode, and the stainless steel barrel was used as the cathode. The micro-arc oxidation power supply parameters adopted the constant voltage mode, and the ratio of the forward voltage to the negative voltage was set to 5:1, and the duty cycle was 45% / 45%. The micro-arc oxidation voltage was 370V, and the treatment time was 12min. After the reaction was completed, the sample was taken out, ultrasonically washed with deionized water for 10s and dried with cold air to obtain a porous micro-arc oxidation film on the surface of the aluminum alloy.

[0028] (3) Electrochemical deposition treatment: a solution containing 0.075 mol / L cerium nitrate hexahydrate (CeN3O9·6H2O), 0.3 mol / L octadecanoic acid (C 18 H 32 O2), a mixed solution of 75ml anhydrous ethanol and 15ml deionized water, the aluminum alloy with a micro-arc oxidation film layer on the surface obtained in step (2) is used as a cathode, and a graphite sheet is used as an anode, and the deposition is carried out at a voltage of 40V for 15min, the electrode spacing is 2cm, and the solution temperature is 50°C. After the reaction is completed, the MAO / ED super-hydrophobic composite film layer is taken out, ultrasonically washed with deionized water for 30s, and dried with cold wind to obtain a MAO / ED super-hydrophobic composite film layer; 3μL of deionized water is taken to test the wettability of the coating surface, and it is found that the contact angle of the water droplet with the surface is 152.3°, and the rolling angle is 5°.

[0029] Embodiment 2

[0030] (1) Surface pretreatment of aluminum alloy: The aluminum alloy substrate was cut into samples of 25 mm × 25 mm × 1 mm, and then the surface was mechanically polished using 240#, 600#, 1000#, 1500#, and 2000# SiC sandpaper in sequence. The samples were then ultrasonically cleaned in deionized water and anhydrous ethanol for 10 min in sequence to remove surface debris and oil stains. The samples were then taken out and dried with cold air.

[0031] (2) Micro-arc oxidation treatment: 2L Na2SiO 3、 The aqueous solution of NaOH and NaF was stirred thoroughly to make it uniformly mixed. The aluminum alloy sample pretreated in step (1) was used as the anode, and the stainless steel barrel was used as the cathode. The micro-arc oxidation power supply parameters adopted the constant voltage mode, and the ratio of the forward voltage to the negative voltage was set to 5:1, and the duty cycle was 45% / 45%. The micro-arc oxidation voltage was 370V, and the treatment time was 12min. After the reaction was completed, the sample was taken out, ultrasonically washed with deionized water for 10s and dried with cold air to obtain a porous micro-arc oxidation film on the surface of the aluminum alloy.

[0032] (3) Electrochemical deposition treatment: a solution containing 0.075 mol / L cerium nitrate hexahydrate (CeN3O9·6H2O), 0.3 mol / L octadecanoic acid (C 18 H 32 O2), a mixed solution of 75ml anhydrous ethanol and 15ml deionized water, the titanium alloy with a micro-arc oxidation film layer on the surface obtained in step (2) is used as a cathode, and a graphite sheet is used as an anode, and the deposition is carried out at a voltage of 45V for 15min, the electrode spacing is 2cm, and the solution temperature is 50°C. After the reaction is completed, the MAO / ED super-hydrophobic composite film layer is taken out, ultrasonically washed with deionized water for 30s, and dried with cold wind to obtain a MAO / ED super-hydrophobic composite film layer; 3μL of deionized water is taken to test the wettability of the coating surface, and it is found that the contact angle of the water droplet with the surface is 155.6°, and the rolling angle is 7°.

[0033] Embodiment 3

[0034] (1) Surface pretreatment of aluminum alloy: The aluminum alloy substrate was cut into samples of 25 mm × 25 mm × 1 mm, and then the surface was mechanically polished using 240#, 600#, 1000#, 1500#, and 2000# SiC sandpaper in sequence. The samples were then ultrasonically cleaned in deionized water and anhydrous ethanol for 10 min in sequence to remove surface debris and oil stains. The samples were then taken out and dried with cold air.

[0035] (2) Micro-arc oxidation treatment: 2L Na2SiO 3、The NaOH and NaF aqueous solutions were stirred thoroughly to make them uniformly mixed. The aluminum alloy sample pretreated in step (1) was used as the anode, and the stainless steel barrel was used as the cathode. The micro-arc oxidation power supply parameters adopted the constant voltage mode, and the ratio of the forward voltage to the negative voltage was set to 5:1, and the duty cycle was 45% / 45%. The micro-arc oxidation voltage was 370V, and the treatment time was 12min. After the reaction was completed, the sample was taken out, ultrasonically washed with deionized water for 10s and dried with cold air to obtain a porous micro-arc oxidation film on the surface of the titanium alloy.

[0036] (3) Electrochemical deposition treatment: a solution containing 0.075 mol / L cerium nitrate hexahydrate (CeN3O9·6H2O), 0.3 mol / L octadecanoic acid (C 18 H 32 O2), a mixed solution of 75ml anhydrous ethanol and 15ml deionized water, the titanium alloy with a micro-arc oxidation film layer on the surface obtained in step (2) is used as a cathode, and a graphite sheet is used as an anode, and the deposition is carried out at a voltage of 50V for 15min, the electrode spacing is 2cm, and the solution temperature is 50°C. After the reaction is completed, the MAO / ED super-hydrophobic composite film layer is taken out, ultrasonically washed with deionized water for 30s, and dried with cold wind to obtain a MAO / ED super-hydrophobic composite film layer; 3μL of deionized water is taken to test the wettability of the coating surface, and it is found that the contact angle of the water droplet with the surface is 152.2°, and the rolling angle is 4°.

[0037] Embodiment 4

[0038] (1) Surface pretreatment of aluminum alloy: The aluminum alloy substrate was cut into samples of 25 mm × 25 mm × 1 mm, and then the surface was mechanically polished using 240#, 600#, 1000#, 1500#, and 2000# SiC sandpaper in sequence. The samples were then ultrasonically cleaned in deionized water and anhydrous ethanol for 10 min in sequence to remove surface debris and oil stains. The samples were then taken out and dried with cold air.

[0039] (2) Micro-arc oxidation treatment: 2L Na2SiO 3、 The NaOH and NaF aqueous solutions were stirred thoroughly to make them uniformly mixed. The aluminum alloy sample pretreated in step (1) was used as the anode, and the stainless steel barrel was used as the cathode. The micro-arc oxidation power supply parameters adopted the constant voltage mode, and the ratio of the forward voltage to the negative voltage was set to 5:1, and the duty cycle was 45% / 45%. The micro-arc oxidation voltage was 370V, and the treatment time was 12min. After the reaction was completed, the sample was taken out, ultrasonically washed with deionized water for 10s and dried with cold air to obtain a porous micro-arc oxidation film on the surface of the titanium alloy.

[0040] (3) Electrochemical deposition treatment: a solution containing 0.075 mol / L cerium nitrate hexahydrate (CeN3O9·6H2O), 0.3 mol / L octadecanoic acid (C 18 H 32O2), a mixed solution of 75ml anhydrous ethanol and 15ml deionized water, the titanium alloy with a micro-arc oxidation film layer on the surface obtained in step (2) is used as a cathode, and a graphite sheet is used as an anode, and the deposition is carried out at a voltage of 45V for 10min, the electrode spacing is 2cm, and the solution temperature is 50°C. After the reaction is completed, the MAO / ED super-hydrophobic composite film layer is taken out, ultrasonically washed with deionized water for 30s, and dried with cold wind to obtain a MAO / ED super-hydrophobic composite film layer; 3μL of deionized water is taken to test the wettability of the coating surface, and it is found that the contact angle of the water droplet with the surface is 152.4°, and the rolling angle is 5°.

[0041] Embodiment 5

[0042] (1) Surface pretreatment of aluminum alloy: The aluminum alloy substrate was cut into samples of 25 mm × 25 mm × 1 mm, and then the surface was mechanically polished using 240#, 600#, 1000#, 1500#, and 2000# SiC sandpaper in sequence. The samples were then ultrasonically cleaned in deionized water and anhydrous ethanol for 10 min in sequence to remove surface debris and oil stains. The samples were then taken out and dried with cold air.

[0043] (2) Micro-arc oxidation treatment: 2L Na2SiO 3、 The NaOH and NaF aqueous solutions were stirred thoroughly to make them uniformly mixed. The aluminum alloy sample pretreated in step (1) was used as the anode, and the stainless steel barrel was used as the cathode. The micro-arc oxidation power supply parameters adopted the constant voltage mode, and the ratio of the forward voltage to the negative voltage was set to 5:1, and the duty cycle was 45% / 45%. The micro-arc oxidation voltage was 370V, and the treatment time was 12min. After the reaction was completed, the sample was taken out, ultrasonically washed with deionized water for 10s and dried with cold air to obtain a porous micro-arc oxidation film on the surface of the titanium alloy.

[0044] (3) Electrochemical deposition treatment: a solution containing 0.075 mol / L cerium nitrate hexahydrate (CeN3O9·6H2O), 0.3 mol / L octadecanoic acid (C 18 H 32 O2), a mixed solution of 75ml anhydrous ethanol and 15ml deionized water, the titanium alloy with a micro-arc oxidation film layer on the surface obtained in step (2) is used as a cathode, and a graphite sheet is used as an anode, and the deposition is carried out at a voltage of 50V for 20min, the electrode spacing is 2cm, and the solution temperature is 50°C. After the reaction is completed, the MAO / ED super-hydrophobic composite film layer is taken out, ultrasonically washed with deionized water for 30s, and dried with cold wind to obtain a MAO / ED super-hydrophobic composite film layer; 3μL of deionized water is taken to test the wettability of the coating surface, and it is found that the contact angle of the water droplet with the surface is 153.4°, and the rolling angle is 5°.

Claims

1. A method for preparing a super-hydrophobic composite film layer on an aluminum alloy surface, characterized in that: The method comprises the following steps: (1) Surface pretreatment of aluminum alloy: The aluminum alloy substrate was cut into appropriate size, its surface was mechanically polished with sandpaper, and the sample was cleaned and dried with cold air. (2) Micro-arc oxidation treatment: Prepare a silicate solution, stir it thoroughly to make it evenly mixed, use the aluminum alloy sample pretreated in step (1) as the anode, and use but not limited to stainless steel as the cathode. The micro-arc oxidation process uses but is not limited to a constant voltage mode, sets the voltage to 200-400V, and the time to 5-30min, and performs micro-arc oxidation treatment on the sample to obtain a porous micro-arc oxidation film layer with a thickness of not less than 6μm on the surface of the aluminum alloy. (3) Electrodeposition treatment: Prepare a solution containing 0.02-0.5 mol / L cerium nitrate hexahydrate (CeN3O9·6H2O), 0.1-1 mol / L octadecanoic acid (C 18 H 32 O2), a mixed solution of anhydrous ethanol and deionized water, the aluminum alloy with a micro-arc oxidation film layer on the surface obtained in step (2) is used as a cathode, and a graphite sheet is used but not limited to it as an anode. The solution temperature is 20-80°C, and electrochemical deposition is performed at a voltage of 30V-60V for 0.1-0.5h to obtain a micro-arc oxidation ceramic film / cerium octadecanoate super-hydrophobic composite film layer.

Citation Information

Cited By

  • Method for micro-arc oxidation of ceramic membrane on basis of t-ZrO2 reinforced aluminum alloy drill rod

    CN121653796A